Social Media Integration for Modern Library and Information Service Promotion - Adnan Ullah (CV Media Inti Teknologi, 2026)
Background:Social media has transformed how academic libraries promote services, digital resources, and communicate with users in the digital era.Aims: This study aims to analyze the role of social media in improving library promotion, digital resource visibility, and user engagement in academic libraries.Methods: This study used a quantitative descriptive survey design involving 253 library professionals in Pakistan, including librarians and library assistants. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using descriptive statistics such as percentages, mean scores, and standard deviations.Result: The findings revealed positive perceptions toward social media use in academic libraries. About 72% of respondents agreed that social media improves user interaction and awareness of library resources, while 72.3% stated that it increases library visibility in the digital era. Additionally, 67.6% believed social media strengthens communication between libraries and users. However, several challenges were identified, including limited staff training, insufficient resources, and inconsistent content updates.Conclusion: The study concludes that social media plays an important role in academic library marketing by enhancing communication, user engagement, and digital service visibility. Libraries should strengthen social media strategies, improve staff digital skills, and provide adequate resources for effective implementation.